Symposium 10: Linking Perceptions of Control and Signs of Engagement in the Process and Content of Collaborative E-Learning - Harris, Rachel; Bolander, Klara; Lebrun, Marcel; Docq, Françoise; Bouvy, Marie-Thérèse (Proceedings of the International Conference on Networked Learning, 2004)
This paper explores various theoretical models relating to control and motivation. Following this, we propose that perception of control is one of the crucial factors influencing motivation and thus engagement with learning. We have focused on individual learners’ perceptions of control and how this might be related to their engagement with collaborative e-learning in terms of process and content. To assess this, we have developed a questionnaire that draws on the many factors that could influence control and motivation. Some preliminary descriptive results from a trial of the questionnaire are briefly outlined.